Equity valuation of Anheuser-Busch InBev S.A./N.V. - Costa, Diogo Horta e (2023)
Anheuser-Busch InBev S.A./N.V. is the largest brewer in the world. The company sells its products in over 150 countries and has leadership positions in most geographies. Like most firms, AB InBev was also affected by the turbulent times of recent years, with the COVID-19 pandemic, the increasing geopolitical tensions, and the inflationary environment. However, as it will be presented in this dissertation, the company is expected to recover in the upcoming years. Through widely used valuation techniques, this dissertation aims to find the fair value per share of AB InBev. AB InBev’s target share price is estimated for the end of next year, and by comparing it with the current share price, an investment recommendation is provided. To come up with an accurate recommendation, a detailed analysis is made not only on the past performance and future perspectives of AB InBev but also on the global macroeconomic environment and the beer industry. Using a DCF approach, a target price per AB InBev share of $70,14 was obtained, resulting in an 11,1% upside potential. To support the DCF method, a sensitivity analysis and a relative valuation (based on comparable companies) were performed. In line with the recommendation provided by the Deutsche Bank’s report, a buy recommendation was issued for AB InBev stock.